2010
DOI: 10.1123/ssj.27.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Power, Politics and “Sport for Development and Peace”: Investigating the Utility of Sport for International Development

Abstract: Sport is currently mobilized as a tool of international development within the “Sport for Development and Peace” (SDP) movement. Framed by Gramscian hegemony theory and sport and development studies respectively, this article offers an analysis of the conceptualization of sport’s social and political utility within SDP programs. Drawing on the perspectives of young Canadians (n = 27) who served as volunteer interns within Commonwealth Games Canada’s International Development through Sport program, the dominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
117
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(137 citation statements)
references
References 40 publications
7
117
2
4
Order By: Relevance
“…However, in recent years, an increasing number of researchers have questioned the strong belief that often exists with regard to the developmental potential of sports (e.g., Coakley, 2011;Coalter, 2007;Darnell, 2007Darnell, , 2010aDarnell, , 2010bGuest, 2009;Kidd, 2008;Levermore, 2008). Giulianotti (2004), for example, referred to these believers as 'sport evangelists' indicating that they lack a critical perspective on sport's actual value.…”
Section: The Promise Of Sportsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in recent years, an increasing number of researchers have questioned the strong belief that often exists with regard to the developmental potential of sports (e.g., Coakley, 2011;Coalter, 2007;Darnell, 2007Darnell, , 2010aDarnell, , 2010bGuest, 2009;Kidd, 2008;Levermore, 2008). Giulianotti (2004), for example, referred to these believers as 'sport evangelists' indicating that they lack a critical perspective on sport's actual value.…”
Section: The Promise Of Sportsmentioning
confidence: 99%
“…As a result, these groups can benefit to a lesser extent from the support provided by social institutions in comparison to other groups. According to Hartmann andKwauk (2011) andDarnell (2010a), there is a need for an alternative approach to developmental sports-based practices that starts by critically looking at existing social hierarchy with its power relations and social inequalities. They labeled this approach "interventionist"; where development is a more radical vision of social change in which participants are empowered to critically take part in the transformation of not only their own experiences of society, but also of society itself.…”
Section: Individual Development Perspectivementioning
confidence: 99%
“…Given the abundant critique in the development literature related to SFD programs that attempt to achieve-and sometimes enforce-change from the outside (e.g., Coalter, 2010;Darnell 2010Darnell , 2012, we as researchers have to acknowledge that findings around the PSP were produced by an international team without permanent local members. We realize that as external researchers, we have both a responsibility and a desire to "do better" in the future, which in this case means expanding the team with local researchers to allow for the implementation of more authentic studies with potentially more meaningful results (see also Sherry, Schulenkorf, & Chalip, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, critics have suggested that as a consequence of external pressures on SFD programs to "perform," there is a tendency to overstate positive program outcomes and associated impacts (Coalter, 2015). Additionally, in the absence of a critical SPORT-FOR-DEVELOPMENT IN THE SOUTH PACIFIC 5 foundation, Darnell (2012) argued that the increasing focus on monitoring and evaluation risks SFD becoming nothing more than a management function, and questions remain about programs' ability to address larger societal constraints and achieve meaningful structural change (see also Coalter, 2010;Darnell, 2010;Hayhurst, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A sport tourist who travels to a mega-event such as the Super Bowl may be motivated to attend as a way to meet famous celebrities, exathletes and others of influence who attend the game. Furthermore, an increasing amount of literature has focused on sport as a catalyst for the development and peace movement (Beutler, 2008;Darnell, 2010;Black, 2010) and the corresponding relationship between sport and politics.…”
Section: Political Orientationmentioning
confidence: 99%